(110) Facet of rutile-structured GeO2: an ab initio investigation. (18th July 2017) - Abbaspour Tamijani, Ali; Ebrahimiaqda, Elham
ABSTRACT: GeO2 is an enticing candidate to replace SiO2 in electronics industry. To date, no work has appeared in the literature specifically focusing on the (110) facet of rutile GeO2 . Density functional theory was applied along with plane-wave approximation to describe the structure and energetics of the (110) plane of tetragonal germanium dioxide. Surface energies were estimated using dispersion-free Perdew–Burke–Ernzerhof (PBE) method as well as dispersion-corrected PBE-D3, D3-corrected revised version of PBE (RPBE-D3), optB88-vdW and optB86b-vdW methods. Atomic displacements with respect to the bulk structure were also reported for slabs relaxed using the aforementioned exchange–correlation functionals. Adsorption energies for weakly bound CO on rutile GeO2 (110) surface were also computed using the above-mentioned methods. Vibrational frequency blue-shift of CO as adsorbed onto rutile GeO2 (110) surface was also predicted. All the calculated values were comparable to the pertinent literature data, either theoretical or experimental, when available. Abstract :